Blood natural killer cells during treatment in recurrent ovarian cancer. (1st November 2020) - Henriksen, Jon Røikjær; Nederby, Line; Donskov, Frede; Waldstrøm, Marianne; Adimi, Parvin; Jakobsen, Anders; Dahl Steffensen, Karina
Abstract: Objective: Recent research indicated favorable prognostic impact of intratumoral natural killer (NK) cells in ovarian carcinoma (OC). The role of NK cells during chemotherapy in OC is unknown. We investigated impact of NK cells in OC patients treated with palliative chemotherapy. Methods: Participants receiving palliative chemotherapy for recurrent OC ( N  = 72) had prospectively blood samples at baseline and before cycle 2. NK cell counts were quantified by flow cytometry. NK cell activity was measured by the NK Vue ® assay, estimating interferon-gamma production. Overall survival (OS) was the primary endpoint. Cutoffs were predefined, NK numbers (≥184 × 10 6 cells/L vs. <184 × 10 6 cells/L) and NK activity (<200 pg/mL vs. ≥200 pg/mL). Results: Median OS in patients with low vs. high NK cell count at baseline was 7.1 months vs. 15.6 months ( p  = .028), respectively, and before cycle 2 was 5.7 vs. 17.3 months, p  < .001, respectively. The difference in restricted mean survival (ΔRMST) was 5.7 months (95% CI: 3.3–8.0) at cycle 2 vs. 2.5 months (95% CI: −0.6 to 5.6) at baseline, showing a significant difference with no overlap of confidence intervals. In multivariate analyses, low NK cell count remained significant with a hazard ratio (HR)=2.83, 95% CI: 1.53–5.22, p  = .001 (baseline) and HR = 3.34, 95% CI: 1.67–6.71, p  = .001 (before cycle 2). Patients with both low NK count and NK activity at baseline ( N  = 20) had median OS 6.5 months vs. 11.5 months in patients with either high activity, high count or both ( p  = .007). In parallel, patients with both low NK activity and count at cycle 2 ( N  = 18) had a median survival of 4.0 months vs. 15.4 months ( p  < .001). Conclusions: A low blood NK cell count in recurrent metastatic ovarian cancer during chemotherapy is associated with unfavorable prognostic impact. Early increase in survival difference based on NK cell status suggests an association between NK cell count and treatment benefit.